INDIVIDUALIZATION OF PEDAGOGICAL PRACTICE AS A MEANS OF IMPROVING THE QUALITY OF PROFESSIONAL TRAINING OF FUTURE TEACHERS OF HISTORY (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the problem of pedagogical practices's individualization as the basis of interaction of intellectual and emonational aspects of educational process and the way of future history teacher's professional education upgrading.
Keywords: pedagogical practice's individualization; professional education; practical student's technological potential